Managing Inclusive Education through the Merdeka Curriculum: Evidence from an Indonesian Special School - Kalsum, Ummu; Muhaemin, Muhaemin; Guntur, Muhammad (International Journal of Asian Education, 2025)
Inclusive education has become an important agenda in global educational reform, and the introduction of the Merdeka Curriculum in Indonesia represents a significant effort to strengthen equitable access for students with disabilities. However, limited research has examined how inclusive education is managed under this new curriculum in special schools. This study aimed to analyze the management of inclusive education through the implementation of the Merdeka Curriculum at SLB Negeri 1 Palopo, focusing on planning, implementation, and evaluation. A qualitative descriptive design was employed, involving the principal, vice principal for curriculum, and teachers as participants, selected purposively for their roles in curriculum management. Data were collected through semi-structured interviews, classroom observations, and document analysis, and analyzed using Miles and Huberman’s interactive model with triangulation to ensure trustworthiness. The results revealed that planning was conducted through the development of Individual Learning Plans (RPI), teacher training, and collaboration with external stakeholders. Implementation emphasized differentiated instruction, project-based learning, and the integration of technology to meet diverse student needs, while evaluation employed authentic and flexible methods such as portfolios, performance tasks, and parental involvement. These findings suggest that inclusive education management in special schools requires multi-stakeholder collaboration, teacher autonomy in instructional strategies, and adaptive evaluation systems. The study provides practical recommendations for strengthening teacher competencies, enhancing collaboration with external partners, and developing authentic assessment approaches to ensure the effective realization of inclusive education goals under the Merdeka Curriculum.